AB1051 Development of a Certified Reference Material for Autoimmune Antibodies (Anti-Myeloperoxidase Immunoglobulin G in Human Serum). (9th June 2015) - Monogioudi, E.; Martos, G.; Hutu, D.P.; Trapmann, S.; Wiik, A.; Meroni, P.; Sheldon, J.; Schimmel, H.; Emons, H.; Zegers, I.
Abstract : Background: The detection and quantification of anti-myeloperoxidase (anti-MPO) IgG antibodies is important for the diagnosis and monitoring of several autoimmune diseases including microscopic polyangiitis and Churg-Strauss syndrome [1]. There is currently significant diversity in the measurement results from different methods and the materials used for calibration. A calibrant has to come with an assigned value that is metrologically traceable, and which is accompanied by an uncertainty statement. Its stability and homogeneity with respect to the certified property must be verified, and the calibrant must be commutable [2]. These attributes are challenging for serum protein calibrants, as they are composed of a mixture of interacting proteins with different isoforms etc. Objectives: This work aimed at producing a new serum protein reference material intended for the standardisation of measurements of anti-MPO IgG antibodies. Methods: For the value assignment of the reference material's concentration, a purified anti-MPO IgG solution was prepared and characterised. Anti-MPO IgG was purified from plasmapheresis material by affinity and size exclusion chromatography. A value for the IgG concentration in this in-house calibrant was assigned using turbidimetry and/or nephelometry selective for total IgG. The property value for the Certified Reference Material (CRM) was obtained by using this anti-MPO IgG calibrant spiked into human serum and routine anti-MPO IgG procedures (ELISA, chemiluminescent and fluoroenzyme immunoassays). In the characterisation procedure 6 dilutions of the target material were measured in parallel to 6 dilutions of the calibrant [3]. Results: Every vial of CRM contains 84 mg/L of anti-MPO IgG (combined expanded uncertainty 9 mg/L, k =2). The estimated uncertainty includes components relating to homogeneity, stability and characterisation. Conclusions: A new serum protein reference material, ERM-DA476/IFCC, was produced. It is homogeneous between and within units and stable under the conditions chosen. The material was characterised by an interlaboratory comparison exercise performed with adherence to ISO/IEC 17025 [4]. The certified value has been established using a purified anti-MPO IgG preparation as calibrant. References: Savige, J et al., Antineutrophil cytoplasmic antibodies and associated diseases: a review of the clinical and laboratory features. Kidney international 57: 846–62, 2000 Approved Guideline, CLSI document C53-A, Clinical and Laboratory Standards Institute, Wayne, PA, USA, 2010 Certification report, Certification of proteins in the human serum. Certified Reference Material ERM® - DA470k/IFCC, European Commission. Joint research Centre, Institute of Reference Materials and Measurements, EUR 23431 EN - 2008 ISO/IEC 17025:2005, International Organization for Standardization, Geneva, Switzerland, 2005 Acknowledgements: The authors would like to thank Håkan Emteborg and Jean Charoud-Got from IRMM for their support related to the processing of this CRM. In addition the support of Emma Tuddenham as well as of IFCC working group (WG-HAT) are warmly acknowledged. Disclosure of Interest: None declared